2022
DOI: 10.1111/1556-4029.15046
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of lethal cyanide poisoning. Analysis by Anion‐Exchange Chromatography with Pulsed Amperometric Detection

Abstract: Cyanide is a poison widely used in cases of suicide or homicide. Although various methods to identify and quantify this substance are reported in the literature, they are mainly validated on biological fluids (e.g., blood and urine). In the present study, the Anion-Exchange Liquid Chromatography with Pulsed Amperometric Detection (IC-PAD) method was validated on blood and, for the first time, on gastric content, and organs (brain, lung, and liver).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Experimental in vitro studies showed that cyanide could be detected up to seven days after death [ 2 ]. Cyanide detection in a decomposed body one year after death has been reported [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental in vitro studies showed that cyanide could be detected up to seven days after death [ 2 ]. Cyanide detection in a decomposed body one year after death has been reported [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of cyanide in experimental conditions and the time intervals are reported [ 2 ]. Cyanide detection in a decomposed body up to one year after death has been reported [ 3 ]. In the present case, hydrogen cyanide has been identified in the postmortem decomposition fluid extracted from the cavities of the interred body approximately three years following burial.…”
Section: Introductionmentioning
confidence: 99%